(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Twenty-two rice lines were used to evaluate salt tolerance at seedling stage. Salinity screening was conducted following IRRI standard protocol and salinized (EC14dS/m) with culture solution at vegetative stage. Initial and final scoring for visual salt injury using the IRRI Standard Evaluation System (SES) was done 21 days after salinization (DAS). Based on 1-9 scale scoring, eight rice genotypes (Binadhan 8, Binadhan 10, FL478, RC217, RC221, RC222, RC225) were found as salt tolerant, five genotypes (RC191, RC192, RC193, RC251, RC249) were identified as moderately tolerant, the rest genotypes were susceptible and the Binadhan 7 was highly susceptible at seedling stage. In seedling stage, Binadhan 8, Binadhan 10, FL478, RC217, RC221, RC222 and RC225 were identified as tolerant, while RC227, RC229, Binadhan 12, Joli Aman, Binadhan 11, BRRI dhan29, Pajam and BRRI dhan39 were found as susceptible. Three selected SSR markers viz. RM7075, RM10701 and RM11504 were used to screen the germplasm for salt tolerance. The highest genetic diversity (0.8967) was observed in loci RM7075 and the lowest gene diversity (0.5537) was found in loci RM10701 with a mean diversity of 0.7231. These SSR markers offer a potential, simple, rapid, and reliable method in marker-assisted breeding and a great impact on identifying salt-tolerant rice genotypes. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 137-147